Business Intelligence : practices, technologies and management - Sabherwal, Rajiv; Becerra-Fernandez, Irma (Hoboken, New Jersey : Wiley & Sons, Inc., 2011)
An introduction to the aspects of business intelligence, including the basic business and technical concepts that are needed, and presents case studies that show how to apply them.
Part I. introduction to business intelligence -- Part II. technologies enabling business intelligence -- Part III. management and future business intelligence.
Includes bibliographical references and index.
Keywords: BUSINESS -- ETHICS